Qualitative Analysis and Control of Complex Neural Networks with Delays - Wang, Zhanshan; Liu, Zhenwei; Zheng, Chengde (Studies in Systems, Decision and Control,, 2016)
This book focuses on the stability of the dynamical neural system, synchronization of the coupling neural system and their applications in automation control and electrical engineering. The redefined concept of stability, synchronization and consensus are adopted to provide a better explanation of the complex neural network. Researchers in the fields of dynamical systems, computer science, electrical engineering and mathematics will benefit from the discussions on complex systems. The book will also help readers to better understand the theory behind the control technique and its design.